A CO‐LIBERATORY FRAMEWORK FOR BIG DATA: with Finley I. Lawson, "The Science and Religion Forum Discuss Information and Reality: Questions for Religions and Science"; Niels Henrik Gregersen, "'The God with Clay': The Idea of Deep Incarnation and the Informational Universe", Michael Burdett and King‐Ho Leung, "The Machine in the Ghost: Transhumanism and the Ontology of Information"; Marius Dorobantu and Fraser Watts, "Spiritual Intelligence: Processing Different Information or Processing Information Differently?"; Matthew Kuan Johnson and Rachel Siow Robertson, "A Co‐Liberatory Framework for Big Data"; Peter M. Phillips, " Digital Theology and a Potential Theological Approach to a Metaphysics of Information"; and Andrew Jackson, "Peacocke Prize Essay—Towards an Eastern Orthodox Contemplation of Evolution: Maximus the Confessor's Vision of the Phylogenetic Logoi." - Johnson, Matthew Kuan; Robertson, Rachel Siow (Zygon: Journal of Religion & Science, 2023)
This article provides an account of the ethical issues that arise when digital technologies and online spaces are structured by Big Data algorithms. We show that although the uses of Big Data may be new, traditional theological and ethical categories are still applicable, including "the sins of the fathers" from hamartiology and the scholastic concept of haecceity. Using these resources, we map the overall ecosystem in which digital technologies are developed and used, identifying the relationships between the individuals and organizations involved. We show how these relationships are often characterized by various kinds of harm. We then argue for a reorientation of the tech ecosystem toward co‐liberation—and ultimately, joy.